2016
DOI: 10.1108/imefm-11-2015-0141
|View full text |Cite
|
Sign up to set email alerts
|

Rental index rate as an alternative to interest rate in Musharakah Mutanaqisah home financing

Abstract: Purpose This paper aims to propose a new pricing alternative called Rental Rate Index (RR-I) that captures the true value of property to be used by Islamic banks in Musharakah Mutanaqisah (MM) contract for home financing. Design/methodology/approach By formulating a profit rate based on Rental Index (RI) and House Price Index (HPI), the proposed rate eliminates conventional profit rate benchmarking, and, at the same time, suggests a fair, equitable and sustainable financing. This new RR-I (measured by RPI/HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…Several studies suggest the use of a rental index as a benchmark for this key parameter in the valuation of MM contracts (Meera and Abdulrazzaq, 2009;Mohd Yusof et al, 2011Yusof et al, 2016). These studies highlight the stability of the rent versus the interest rate and its correlation with economy.…”
Section: Rentmentioning
confidence: 99%
“…Several studies suggest the use of a rental index as a benchmark for this key parameter in the valuation of MM contracts (Meera and Abdulrazzaq, 2009;Mohd Yusof et al, 2011Yusof et al, 2016). These studies highlight the stability of the rent versus the interest rate and its correlation with economy.…”
Section: Rentmentioning
confidence: 99%
“…At the same time, it would remain competitive with the conventional banking as the rates are comparable, without relying on and being benchmarked against the interest rates. (Yusof, Mahfudz, Arif, & Ahmad, 2016) From the interview, it was found that MM Home Financing is offered to both the housing projects under construction and the completed houses. As the risk taken by the bank in offering MM Home Financing for houses under construction is higher, the bank is stricter and more careful in choosing the house developer before giving the customers the contract.…”
Section: Recommendationsmentioning
confidence: 99%
“…Musharakah Mutanaqisah (MM) is a diminishing partnership concept that comprises three contracts which are Musharakah (partnership), Ijarah (renting) and Bay` (sales) (Abdullah, 2016;Smolo and Hassan, 2011;Yusof et al, 2016). This hybrid contract has been defined by Bank Negara Malaysia (BNM) as "a contract of partnership that allows one (or more) partner(s) to give a right to gradually own his share of the asset to the remaining partners based on agreed terms" (BNM, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One critique against BBA is its use of Bay-Al-Inah (buy-back sale), that is forbidden by majority schools of thoughts except by Shafi'is (Smolo and Hassan, 2011). As BBA financing is collateralized, Islamic banks earn more profits with less risk and efforts using BBA mode of finance (Abdullah, 2016;Smolo and Hassan, 2011;Yusof et al, 2016). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation